The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18182/tjf.10489
|View full text |Cite
|
Sign up to set email alerts
|

Kuzeydoğu Cezayir’de mantar meşesi meşcerelerinde Coleoptera envanteri

Abstract: Laid Ouakid a , Abdelkrim Tahraoui a Résumé : La faune entomologique est un élément essentiel dans la dynamique et le fonctionnement des écosystèmes forestiers. Le rôle écologique ainsi que le caractère bio-indicateur de certaines espèces d'insectes peuvent indiquer l'état sanitaire des forêts et déterminer certains facteurs liés à la dégradation de celles-ci. Au niveau des subéraies Algériennes, de nombreuses attaques d'insectes touchant principalement les feuilles, les fruits ainsi que le tronc du chêne ont … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Larvae grow in the small living layer just under the bark, https://doi.org/10.17221/77/2021-JFS where the sap circulates and where cork is made, as for Lymantria dispar (spawning, aged caterpillars and chrysalises) (Villemant, Fraval 1993). In addition, Daas et al (2016) reported that the larvae of several Scarabaeidae develop in the rotten wood of old oaks (injured or even dead), as well as in stumps, and in the compost that forms in their hollows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larvae grow in the small living layer just under the bark, https://doi.org/10.17221/77/2021-JFS where the sap circulates and where cork is made, as for Lymantria dispar (spawning, aged caterpillars and chrysalises) (Villemant, Fraval 1993). In addition, Daas et al (2016) reported that the larvae of several Scarabaeidae develop in the rotten wood of old oaks (injured or even dead), as well as in stumps, and in the compost that forms in their hollows.…”
Section: Discussionmentioning
confidence: 99%
“…Such biotic agents include insect pests which attack leaves, fruits and trunks. According to Daas et al (2016), the action of some phytophagous beetles (e.g., Curculionidae, Tortricinae and Lymantriinae) is one of the main causes of defoliation; xylophages weaken the trees, and gland pests have a direct impact on regeneration.…”
mentioning
confidence: 99%
“…Tribe Cetoniini Leach, 1815 Oxythyrea funesta Poda von Neuhaus, 1761 Regional distribution: from the Mediterranean coast to the northern edge of the Sahara (Baraud, 1985;Mitter, 2011;Chavanon et al, 2015;Tamadouni and Arahou, 2017;Vondráček et al, 2018;Chavanon, 2020). General distribution: Palaearctic species: most of Europe up to the Ural Mountains and the Caucase, North Africa, Cyprus, Iran, Kazakhstani, Turkey and West Siberia (Bunalski, 1999;Silfverberg, 2004;Šablevičius, 2004Bukejs et al, 2006;Horak et al, 2009Horak et al, , 2013Pivotti et al, 2011;Barclay and Notton, 2013;Tamutis and Dapkus, 2014;Daas et al, 2016;Thomaes et al, 2016;Löbl and Löbl, 2016;Vondráček et al, 2018;Zemouri et al, 2021).…”
Section: Family Scarabaeidae Subfamily Cetoniinae Leach 1815mentioning
confidence: 99%